Arithmetic Adventure: A Role-Playing Game to Support Students’ Mathematical Thinking on Arithmetic Sequences - Nurrosyadah, Naqiyyah; Susanti, Ely; Somakim, Somakim (Universitas Muhammadiyah Mataram, 2026)
This study aims to develop an educational Role-Playing Game (RPG) entitled Arithmetic Adventure: The Mystery of Polaria Village to support students’ mathematical thinking on arithmetic sequences. The research employed a Development Research approach using the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation stages. The subjects were 10th-grade students of SMA Negeri 10 Palembang who had implemented the Merdeka Curriculum. Data were collected through expert validation, student practicality questionnaires, and mathematical thinking ability tests. The results indicated that the RPG obtained an overall average validity score of 4.45, categorized as very valid in terms of content, construct, language, and ICT aspects. Practicality testing showed an average percentage of 86.25%, placing the RPG in the very practical category. Furthermore, the potential effect test revealed that 48.6% of students achieved good, 28.6% very good, and 22.9% fair in mathematical thinking ability, showing improvements in specializing, generalizing, conjecturing, and convincing. These findings demonstrate that Arithmetic Adventure is a valid, practical, and potentially effective educational game for supporting students’ mathematical thinking in arithmetic sequences. The study provides theoretical contributions by reinforcing the role of RPGs in fostering mathematical thinking and practical contributions by offering an innovative alternative medium for mathematics learning.